Visible-light-triggered generation of persistent radical anions from perylenediimides: A substituent effect and potential application in photocatalytic reduction of Ag+. (June 2019) - Liu, Hongliang; Yin, Gengwen; Li, Qizhe; Liu, Gang; Pu, Shouzhi; Zhang, Haiquan
Abstract: Three perylenediimide derivatives were reduced to their persistent radical anions in N-methyl-2-pyrrolidone (NMP) under ambient conditions by a visible light photoinduced electron transfer (PET). UV–vis and electron paramagnetic resonance (EPR) measurements were carried out to confirm the formation of radicals. The relationships between molecular structure, electrochemical property, phototransformation kinetics, and air stability of radical anions were investigated by the introduction of pyrimidine rings at the core position and fluoroalkylation substituents at the imide position. This study reveals that the electron-deficient pyrimidine rings and electron-withdrawing fluoroalkylation substituents can effectively enhance the phototransformation rate and the radical stability at ambient conditions. The effects of solvents and illuminance levels on the photoinduced reduction of perylenediimides were also studied. A photocatalytic reduction of Ag + was successfully carried out using the perylenediimide with pyrimidine and fluoroalkylation substituents as catalyst upon irradiation with visible light. Graphical abstract: A series of perylenediimide derivatives (PDIs) were successfully synthesized for the generation of visible-light-triggered persistent organic radical anions in NMP and under ambient conditions that is highly dependent on the substituents. An application of the visible light photocatalytic reduction of Ag + using PDI 2 − was successfully explored to recovery of elemental silver in NMP. Image 1 Highlights: Three PDIs were reduced to their persistent radical anions by visible light irradiation under ambient conditions. The pyrimidine rings and fluoroalkylation substituents can effectively enhance the radical stability. The visible light photocatalytic reduction of Ag + using PDIs was first successfully explored to recovery of elemental Ag.